1987
DOI: 10.1515/znc-1987-0414
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Hydroxylation of Cedrol and Cedrene

Abstract: Biotransformation of cedrol with 5 different strains afforded 8 previously undescribed hydroxy-cedrols. The attack came from a hemisphere centered at C-12 approximately. At two positions epimeric pairs were formed, which could be avoided by using different strains. Contrary to previous studies of other groups we found the 2-and 12-hydroxylations as main reactions. Cedrene needed prolonged fermentation and gave lower yields than cedrol. Apart from allylic hydroxylations the oxidation pattern by Corynespora cass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…α-Cedrene is a major component of cedar wood oil which is used widely as a perfume and as a precursor of synthetic perfumes for toiletry and cosmetic products. Abraham and coworkers reported that Corynespora cassicola DSM 62474 and Rhodococcus rhodochrous (formerly Mycobacterium rhodochrous) ATCC 999 converted a-cedrene to a variety of minor products, such as 3-hydroxy-and 12-hydroxy-a-cedrenes (Abraham et al 1987) and cedrenone and 10-methoxy-a-ce-drene, respectively (Kieslich et al 1986). The formation of such products from a-cedrene by Beauveria sulfurescens ATCC 7159 was also reported (Lamare et al 1987;Lamare and Furstoss 1990) However, the biotransformations of a-cedrene reported thus far require a long cultivation time, and the yields of products have been extremely low.…”
Section: Discussionmentioning
confidence: 99%
“…α-Cedrene is a major component of cedar wood oil which is used widely as a perfume and as a precursor of synthetic perfumes for toiletry and cosmetic products. Abraham and coworkers reported that Corynespora cassicola DSM 62474 and Rhodococcus rhodochrous (formerly Mycobacterium rhodochrous) ATCC 999 converted a-cedrene to a variety of minor products, such as 3-hydroxy-and 12-hydroxy-a-cedrenes (Abraham et al 1987) and cedrenone and 10-methoxy-a-ce-drene, respectively (Kieslich et al 1986). The formation of such products from a-cedrene by Beauveria sulfurescens ATCC 7159 was also reported (Lamare et al 1987;Lamare and Furstoss 1990) However, the biotransformations of a-cedrene reported thus far require a long cultivation time, and the yields of products have been extremely low.…”
Section: Discussionmentioning
confidence: 99%
“…Abraham and coworkers (1,11) reported that R. rhodochrous ATCC 999 converted ot-cedrene to cedrenone and 10-methoxy-a-cedrene with very low yields (<1%), but they did not describe the reaction conditions or provide spectral data for the products. To confirm their studies, we tried to transform a-cedrene by using R. rhodochrous ATCC 999 under both growing and resting conditions, but we failed to detect such products.…”
Section: Discussionmentioning
confidence: 99%
“…Cedrol was chosen as model compound because of the commercial interest from industry and because its bioconversion is well described Trifilieff et al, 1975;Abraham et al, 1987;Hanson & Nasir, 1993;Maatooq et al, 1993;Gand et al, 1995;Miyazawa et al, 1995Miyazawa et al, , 2003Fraga et al, 1996;Aleu et al, 2001;Collins & Reese, 2001). As initial orienting experiment, cedrol was added as substrate to transformed E. coli cells with a total volume of 1 mL.…”
Section: Bioconversion Of Cedrolmentioning
confidence: 99%